Recent confirmed records of Galictis vittata in the department of Sucre, Caribbean region of Colombia - Salcedo-Rivera, Gerson A.; De la Ossa-V., Jaime; Ballesteros-Correa, Jesús; González-Maya, José F.; Chacón-Pacheco, Julio (Therya Notes, 2020)
Galictis vittata is a small carnivore distributed in all the natural regions of Colombia, but it is considered as a “demographic rarity” due to its low density throughout its range in the national territory. This note documents new records with some ecological data and compiles the existing evidence about the local distribution of G. vittata in the department of Sucre, Colombian Caribbean. The new records are the product of fieldwork aiming at evaluating mammal diversity in the region, among other ecological aspects, by applying camera-trapping and interviews. In addition, other confirmed records of the species in the department were compiled based on the available information in three online data portals. The new records of G. vittata presented include a camera-trap record in a disturbed area of tropical dry forest and one related to an event of attack by domestic dogs. The local distribution of the species is extended to the sub-regions of Golfo de Morrosquillo and San Jorge, based on that three preserved specimens confirm its presence in the Montes de María sub-region. This is among the first data compilation of G. vittata focused specifically to the department of Sucre, also confirming its current presence in disturbed zones of tropical dry forest. The new records contribute evidence to previous statements about the potential ecological tolerance of the species to landscape modifications and provide novel information on possible threats and habitat use, specially about the potential importance of some elements in fragmented landscapes.